Role of PCSK5 Expression in Mouse Ovarian Follicle Development: Identification of the Inhibin α- and β-Subunits as Candidate Substrates - Antenos, Monica; Lei, Lei; Xu, Min; Malipatil, Anjali; Kiesewetter, Sarah; Woodruff, Teresa K. (PLOS ONE, 2011)
Inhibin and activin are essential dimeric glycoproteins belonging to the transforming growth factor-beta (TGFβ) superfamily. Inhibin is a heterodimer of α- and β-subunits, whereas activin is a homodimer of β-subunits. Production of inhibin is regulated during the reproductive cycle and requires the processing of pro-ligands to produce mature hormone. Furin is a subtilisin-like proprotein convertase (proconvertase) that activates precursor proteins by cleavage at basic sites during their transit through the secretory pathway and/or at the cell surface. We hypothesized that furin-like proconvertases are central regulators of inhibin α- and β-subunit processing within the ovary. We analyzed the expression of the proconvertases furin, PCSK5, PCSK6, and PCSK7 in the developing mouse ovary by real-time quantitative RT-PCR. The data showed that proconvertase enzymes are temporally expressed in ovarian cells. With the transition from two-layer secondary to pre-antral follicle, only PCSK5 mRNA was significantly elevated. Activin A selectively enhanced expression of PCSK5 mRNA and decreased expression of furin and PCSK6 in cultured two-layer secondary follicles. Inhibition of proconvertase enzyme activity by dec-RVKR-chloromethylketone (CMK), a highly specific and potent competitive inhibitor of subtilisin-like proconvertases, significantly impeded both inhibin α- and β-subunit maturation in murine granulosa cells. Overexpression of PC5/6 in furin-deficient cells led to increased inhibin α- and βB-subunit maturation. Our data support the role of proconvertase PCSK5 in the processing of ovarian inhibin subunits during folliculogenesis and suggest that this enzyme may be an important regulator of inhibin and activin bioavailability.